2001
DOI: 10.1074/jbc.m006535200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Endothelial Nitric-oxide Synthase by Tumor Necrosis Factor-α

Abstract: Cell death via apoptosis induced by tumor necrosis factor-␣ (TNF-␣) plays an important role in many physiological and pathological conditions. The signal transduction pathway activated by this cytokine is known to be regulated by several intracellular messengers. In particular, in many systems nitric oxide (NO) has been shown to protect cells from TNF-␣-induced apoptosis. However, whether NO can be generated by the cytokine to down-regulate its own apoptotic program has never been studied. We have addressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 57 publications
7
88
0
Order By: Relevance
“…The authors found that TNFα activated eNOS through ceramide formation. Generation of NO in this system was anti-apoptotic (Bulotta et al, 2001). These conflicting results highlight the dual effects that RNI and indeed ROS can have in different cells.…”
Section: Receptorsmentioning
confidence: 72%
“…The authors found that TNFα activated eNOS through ceramide formation. Generation of NO in this system was anti-apoptotic (Bulotta et al, 2001). These conflicting results highlight the dual effects that RNI and indeed ROS can have in different cells.…”
Section: Receptorsmentioning
confidence: 72%
“…Zhang et al directly measured NO levels in the intact endothelium of coronary arteries by using realtime fluorescence microscopy and found NO levels were reduced in ceramide-treated vessels [70]. Cell culture studies have shown that ceramide reduces the release of bioactive NO in human umbilical vein endothelial cells [73,74]. Overwhelming evidence demonstrates that ceramide-induced oxidative stress may be the major reason for its effects on the reduction of NO bioavailability and endothelial dysfunction.…”
Section: Ceramide Smase and Nitric Oxide (No)mentioning
confidence: 99%
“…NOS III activation can involve ceramide generation by either acid or neutral sphinomyelinases, stimulated either by basic fibroblast growth factor (bFGF) in CHO-K1 cells (Goldkorn et al, 1998). It can also involve tumor necrosis factor-α (TNF-α) in HeLa cell clones transfected with NOS III under a tetracycline-responsive element (Barsacchi et al, 2003;Bulotta et al, 2001). NOS III activation by TNF-α requires stimulation of the phosphatidylinositol 3 kinase (PI3K)/Akt pathway while bFGF activated NOS III is independent of PI3/Akt activation.…”
Section: Ceramide and Apoptosismentioning
confidence: 99%